A nonviral vector with transfection activity comparable with adenoviral transduction. (November 2016) - Cheung, Jennifer; Chino, Takahiro; Co, Cynthia; Konopka, Krystyna; Düzgünes, Nejat
Aim: Viral vectors are used commonly in gene therapy trials, but their potential toxic effects are a serious concern. Identification of highly efficient nonviral vectors may alleviate these effects.Results & methodology: We compared the abilities of TransfeX, TransIT-LT1 and adenovirus to deliver the firefly luciferase and green fluorescent protein genes into HeLa cervical carcinoma, and HSC-3 and H357 oral squamous cell carcinoma cells. TransfeX mediated fourfold higher gene expression in HeLa cells than adenovirus, even at the highest multiplicity of infection. Flow cytometry indicated that a population of transfected cells expresses higher levels of green fluorescent protein than transduced cells.Conclusion: TransfeX may be useful for gene therapy applications, particularly where the use of adenovirus is contraindicated.